LAPAROSCOPIC RADICAL CYSTECTOMY WITH ILEAL CONDUIT URINARY DIVERSION, FIRST EXPERIENCE IN BANDUNG - Jouwena, Davis Roland Gustav; Pramod, Sawkar Vijay (Indonesian Journal of Urology, 2015)
Objective: To report our experience in performing laparoscopic radical cystectomy with ileal conduit urinary diversion (extracorporeal reconstruction). Material & method: This study was take place in Hasan Sadikin Hospital Bandung. A 54-year-old male with histologically proven transitional cell carcinoma of the bladder cT2bN0M0 underwent a laparoscopic radical cystoprostatectomy and ileum dissection was performed under laparoscopy. Ileal conduit and stoma reconstruction performed extracorporeal through small incision between ports (about 4cm). Results: The surgical margins were free of disease. The operative time was 360 minutes. Estimated blood loss was 600cc. Hospital stay was 5 days. Patient was discharge with no complication of post-op wound, and urine production about 1500cc/24hrs via stoma. Conclusion: Laparoscopic radical cystectomy with ileal conduit extracorporeal reconstructive urinary diversion could be the preferred means in managing bladder tumor on selective case.